Long-term outcome after transcatheter aortic valve implantation. Issue 12 (5th February 2015) - Bouleti, Claire; Himbert, Dominique; Iung, Bernard; Alos, Benjamin; Kerneis, Caroline; Ghodbane, Walid; Messika-Zeitoun, David; Brochet, Eric; Fassa, Amir-Ali; Depoix, Jean-Pol; Ou, Phalla; Nataf, Patrick; et al.
Abstract : Objective: To assess late outcome after transcatheter aortic valve implantation (TAVI) up to 6 years and to analyse its predictive factors with a particular emphasis on functional status. Very few data exist on the long-term results of TAVI, and these data are crucial for decision making. Methods: Between October 2006 and December 2009, 123 consecutive patients were discharged alive after TAVI in our institution. Mean age was 82±8 years, and 88% of patients were highly symptomatic in New York Heart Association (NYHA) class III–IV. Results: Follow-up was complete in 122 patients (99%). The overall 6-year survival rate was 31%±5%, the majority of deaths being non-cardiac. Predictive factors of late mortality were the presence of lower limb arteritis (p=0.009), a higher Charlson comorbidity index (p=0.03) and post-TAVI paraprosthetic aortic regurgitation ≥2/4 (p=0.01). Late outcomes according to Valve Academic Research Consortium-2 criteria were analysed, and the 5-year event-free survival rate was 28%±4%. Finally, the rate of good functional results, defined as survival in NYHA class I or II, was 32%±5% at 5-year follow-up. In the survivors, the EQ-5D questionnaire further confirmed the benefit in terms of quality of life. Conclusions: About one-third of patients discharged alive after TAVI were alive at 6-year follow-up, and the survivors exhibited good functional results assessed by NYHA class and quality-of-life standardised evaluation.